Rheumatological complaints in H syndrome: from inflammatory profiling to target treatment in a case study - Alessandra Tesser; Erica Valencic; Valentina Boz; Gianluca Tornese; Serena Pastore; Manuela Zanatta; Alberto Tommasini (Pediatric Rheumatology Online Journal, 2024)
Abstract Background H Syndrome is a rare genetic condition caused by biallelic pathogenic variants in the SLC29A3 gene. It is characterized by a wide range of clinical manifestations, many of which are related to the immune-rheumatological field. These include scleroderma-like skin changes, deforming arthritis, and enlarged lymph nodes. The condition also features cardiac and endocrine defects, as well as hearing loss, for which the immune pathogenesis appears less clear. Immunomodulatory medications have been shown to improve many symptoms in recent experiences. Case presentation A 21-year-old girl was referred to our institute after being diagnosed with H syndrome. Her medical history was characterized by the development of finger and toe deformities, which developed since the first years of life and progressively worsened with clinodactyly. At 6 years of age, she was diagnosed with diabetes mellitus without typical autoantibodies and with bilateral sensorineural hearing loss. She also complained of frequent episodes of lymphadenopathy, sometimes with colliquation and growth retardation due to pancreatic insufficiency. It wasn’t until the genetic diagnosis of H syndrome that the continual increase in acute phase reactants was noticed, suggesting that an immunological pathogenesis may be the source of her problems. During her visit to our institute, she reported serious pain in both feet and hands and difficulty walking due to knee arthritis and muscle contractures. Conventional therapy with steroid injection in affected joints and methotrexate only led to partial improvement. After a thorough assessment of her inflammatory profile showing a high interferon score, the girl received treatment with baricitinib. Furthermore, based on recent data showing that SLC29A3 deficiency results in interferon production because of Toll-like Receptor 7 activation in lysosomes, hydroxychloroquine was also added. The combination of the two drugs resulted for the first time in a rapid and persistent normalization of inflammatory markers, paralleled by a dramatic improvement in symptoms. Conclusions We describe the results of inhibiting IFN inflammation in H syndrome and discuss how JAK inhibitors and antimalarials might represent a mechanistically based treatment for this orphan drug disorder.